Estado digital: Serviços digitais públicos e assimetrias federativas - Elder Patrick Maia Alves (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– We began this work by describing and analyzing socio-digital inequalities. Next, an analysis of the supply of public digital services offered by the federal government is made. Finally, we analyzed the supply of public digital services offered by municipalities. Through a set of secondary and primary data, we found that Brazilian municipalities offer a set of public digital services, which are, for the most part, of a final nature, such as medical consultations and school registrations. This offer is part of a broad framework, which determines the supply and quality of these services. This framework is made up of three factors: i) socio-digital inequalities; ii) federative asymmetries; and iii) and the different state capacities that exist between the Union, states and municipalities. It was found that the provision of public digital services is at an advanced stage by the federal government, although with some difficulties and problems, but quite irregular and incipient among municipalities - although it has also advanced. This aspect occurs mainly because the inter-federative coordination carried out by the federal government to build the digital government in Brazil used few mechanisms characteristic of market logic, such as financial incentives and credit facilitation.
Keywords: O; O3; O38; 330; digital public services; socio-digital inequalities; federative asymmetries; state capacities; instruments and mechanisms of inter-federative coordination